Pengaruh Persepsi Mahasiswa Tentang Keterampilan Mengajar Dosen Dan Motivasi Belajar Terhadap Kreativitas Belajar Pada Mata Kuliah Kewirausahaan Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Tahun 2015/2016 - Fazrin, Adhinika Aullyna; , Drs. Djoko Suwandi, M.Pd (2016)
This study aimed to analyze the influence of students' perceptions of faculty teaching skills and learning motivation toward learning creativity. The sample in this study is the Accounting Education students who take entrepreneurship courses totaling 119 students. Data analysis technique used is multiple linear regression, t-test, F, Effective and Relative Contribution. Based on the survey results revealed that there is influence students' perceptions of faculty teaching skills and learning motivation toward learning creativity in entrepreneurship courses the Faculty of Education University of Muhammadiyah Surakarta Year 2015/2016. The relative contribution (SR) amounted to 85.6% and the effective contribution (SE) of 45.3% on student perceptions of faculty teaching skills to learn creativity. The relative contribution (SR) of 14.4% and the effective contribution (SE) of 7.6% on the creativity learning motivation towards learning.